The crisis in the foreign exchange market - Michael Melvin; Mark P. Taylor (Center for Economic Studies and ifo Institute (CESifo), 2009)
The financial crisis of 2007-2008 had major implications for the foreign exchange market. We review events and implications for exchange rates, volatility, returns to currency investing, and transaction costs. This blow-by-blow narrative is intended to be a resource for researchers seeking a comprehensive review of the what, why and when of the financial crisis in terms of foreign exchange market dynamics. An implementable financial stress index (FSI) is created and then used to illustrate the dramatic nature of the current crisis compared to earlier crises. We also examine how the global FSI might have been used to condition the exposure to the carry trade (long high interest rate currencies, short low interest rate currencies) and we show that such an index has potential value in protecting a portfolio against loss during periods of stress, although this result is subject to the important caveats of controlling for transaction costs and timely recognition of the change in regime.
Keywords: F30; F31; 330; financial crisis; foreign exchange; exchange rates; transaction costs; Finanzmarktkrise; Devisenmarkt; Wechselkurs; Volatilität; Kapitalertrag; Transaktionskosten; Internationaler Finanzmarkt; Risiko; Index; Welt